Design and evaluation of a Quadratic Buck Converter - Siripan Trakuldit (Elsevier, 2022)
This paper presents design and evaluation of a Quadratic Buck Converter (QBC). A step-by-step procedure to select the converter’s component values and semiconductor device ratings is demonstrated. A prototype QBC with a simple closed loop output voltage control is constructed and experimentally evaluated. It is shown that the converter performs well within the design specification, has good output voltage regulation and fast transient response, and achieves the highest efficiency of 82%.